HOLISTIC DEVELOPMENT AND SECURITY FOR ESSZONE - Peters, Diana; Chan, Jennifer Kim Lian; Gusni Saat; Abentim Estim; Sebastian, Martin A. (Penerbit Universiti Malaysia Sabah, 2019)
This book is an attempt to contextualise the issues occurring in this part of the region which is not only solely constrained by security in the traditional sense, but also to ensure the livelihoods of citizens are being protected. The four pillars for a holistic approach identified in this book are based on the inputs by stakeholders in four workshops organised in throughout 2016, under the same theme. It is realised that the challenges to the security of Eastern Sabah has many faces – piracy, illicit trafficking, and kidnappings – and these challenges are evolving. As such, an all-encompassing solution is needed.